(untitled) (MAUSAM, 2011)
Aerosols are known to cause important effects on weather and climate of Polar Regions and their radiation balance of the polar surface-atmosphere system, especially in the regions characterized by high surface-reflectance conditions, which also prevails the heterogeneous chemistry of aerosols. Therefore, the knowledge of the aerosol physical and optical properties needs to be improved on both spatial and temporal scales. To characterize these physico-chemical and optical properties, studies have been carried out over both the polar regions [Antarctica (‘Maitri’ (70.76oS, 11.74oE) and Arctic “Himadri” (79°N, 11°E) during the summer period of 24th (2004-05), 26th (2006-07) Indian Antarctica Expedition, and during 14th Indian Arctic Expedition in 2010. Total column aerosol optical depth (AOD), ozone (TCO), precipitable water content (PWC), and direct radiative forcing using a multi-channel solar-radiometer (Microtops II); and short-wave global radiative flux using a wide-band pyranometer for their characteristics. In the Arctic, an Andersen Sampler, Black Carbon Aethalometer was also operated to determine the chemical properties of aerosols. The aerosol optical, physical and radiative properties, and their interface with simultaneously measured gases and their chemical composition have been investigated. The results showed that the daily mean AOD at a characteristic wavelength of 500 nm was found to be 0.042 with an average Angstrom coefficient of 0.24, revealing abundance of coarse-mode particles in Antarctica, and Arctic average AOD was observed 0.11 with an average Angstrom coefficient of 2.84, suggesting fine-mode particles. The TCO measured by the surface-based ozone monitor matched reasonably within 5% with that of the Total Ozone Mapping Spectrometer (TOMS) satellite sensor. Variability in ozone on daily scale, during the study period, was less than 4% over the Antarctica region and more or less same for Arctic. The January 2005 fluxes were found to be less by about 20% as compared to those in February 2005. The average short-wave direct radiative forcing due to aerosols showed cooling at the surface with an average value of -0.47 W/m2 during the study period. In this paper, we briefly describe the equipment deployed, data archival, their analysis techniques and salient results obtained over the Indian polar stations, ‘Maitri’ and ‘Himadri’.